Prevalencia de las infecciones respiratorias bajas en niños menores de 5 años atendidos en el hospital de zumba parroquia zumba. Año 2015 - Banegas Torres, Yadira Paola (2016)
This research work was to determine the prevalence of low in children under 5 treated at the Hospital Zumba for compliance he raised the following methodology respiratory diseases: descriptive, transversal, literature, field, retrospective. Survey techniques and observation with his instrument the questionnaire and the observation guide to the 62 children under 5 the following results were obtained prevalence of lower respiratory infections is 14.58% was applied. The conditions that prevail is Pneumonia with 41.94%, with 37.10% bronchiolitis and bronchitis with 20.97%. besides the socioeconomic conditions of children age 3-5 with 69.35%, male 53.23% with average socioeconomic level with 80% and low with 20% of urban origin 85.48%, occupancy was investigated of mothers it is that domestic doings with 43.55% among the factors that influence the environmental lower respiratory tract infections with 60.88% were exposed to sudden temperature changes in socioeconomic are the low level of education with 3.76%; in nutritional are the lack of exclusive breastfeeding with 29.03%. Based on these results the author implemented a plan of action based on the same educational activities consisted of theoretical training and delivery of information material and home to the most vulnerable places visits took place. Concluding that the prevalence of respiratory infections in children under 5 years is 14.58% and the main causes are sudden changes in temperature, low education, exposure to smoke, and lack of breastfeeding. Keywords: Prevalence, respiratory infections, children under 5 years